Clique-based socially-aware intelligent message forwarding scheme for delay tolerant network. (2018) - Juyal, Vandana; Saggar, Ravish; Pandey, Nitin
Delay tolerant network (DTN) is a challenged class of mobile ad hoc network that allows unbounded delay and intermittent contacts. In such a network the routing strategies involve storing a message and forward it to some future contact. In the past, most of the strategies defined were flooding based that eventually creates multiple duplicate copies of a message. This leads to the consumption of most of the network resources like energy, buffer space, processing power, etc. For this, we have extended our previous work based on artificial neural network based forwarding using trust value, which has potential to diminish these issues. Using trust as a modelling factor, we propose a trusted DTN clique which is socially aware and intelligently forwards in DTN. The work is examined using extensive simulation on real-world external traces. Also, the work is compared with existing routing protocols namely Prophet, SprayAndWait, and EpidemicOracle. The performance metric chosen for the proposed algorithm are messages aborted, messages relayed and messages dropped. Experimental results show that the proposed algorithm limits the number of message copies relayed in the DTN network and further provides a light weight intrinsic security to the DTN nodes.